Exploring the Impact of Helicobacter pylori and Potential Gut Microbiome Modulation - Isaac Jingkhai Ong; Ke-Yan Loo; Lydia Ngiik-Shiew Law; Jodi Woan-Fei Law; Loh Teng-Hern Tan; Vengadesh Letchumanan (Progress in Microbes and Molecular Biology)
Helicobacter pylori is a highly prevalent bacteria that can harm humans due to its major involvement in developing gastrointestinal diseases, particularly gastric cancer. Therefore, eradicating H. pylori is one of the most important strategies for preventing gastric cancer. Antibiotic treatment has always been the gold standard treatment for H. pylori infection. However, the decreasing efficacy of antibiotic therapy due to the rising antibiotic resistance and high incidence of dysbiosis-related adverse effects resulted in eradication failure. To enhance the effectiveness of antibiotic therapy, strategies that modulate the gut microbiome were proposed to play a positive role. Generally, the integration of probiotics or symbiotic into antibiotic therapy was shown to enhance the eradication rate and reduce the incidence of adverse effects. This review aims to discuss the role and effect of H. pylori in gastric carcinogenesis and gut microbiome modulation in eradicating H. pylori infection.